Building Voluntary Pension Schemes in Emerging Economies - Rudolph, Heinz P. (World Bank, Washington, DC, 2016)
After the financial crisis, some Central and Eastern Europe countries partially or totally reversed the pension reforms they had initiated in the previous two decades. In the presence of an aging population in the region, reductions in replacement rates will be the most likely adjustment mechanism for the social security systems to remain fiscally sustainable. In some other emerging economies, mandatory funded schemes are operating with low contribution rates, and policy makers have not been able to pass legislation to increase the contribution rate to ensure adequate pensions for future retirees. Voluntary pension schemes that take into consideration the behavioral aspects of individuals may provide a viable solution for countries that need to increase retirement savings but face political resistance to mandatory increases in contribution rates. The proposed mechanism shifts the focus of voluntary pension plans from "opt-in" to "opt-out" schemes. The emphasis is in setting the default options in a way that employees have to make an explicit decision if they do not want to contribute to the pension system. The paper builds on the experiences of several countries, including Italy, New Zealand, the United Kingdom, and the United States, and proposes policy recommendations and good practices for building voluntary pension systems. These opt-out schemes should be able to provide high coverage among white and blue collar workers, and consequently improve the future pensions of individuals.